Photophysics of isomerizable Re(I) complexes: a theoretical analysis - Kayanuma, Megumi; Daniel, Chantal; Köppel, Horst; Gindensperger, Etienne (Coordination chemistry reviews, 2011)
A theoretical exploration of the trans-cis photoisomerization of the 4-styrylpyridine (stpy) and 1,2-bis(4-pyridyl)ethylene (bpe) ligands L in [Re(CO)3(bpy)(L)]+ (bpy=2,2′-bipyridine) complexes is performed on the basis of first-principles quantum chemical methods. The spin-orbit theoretical electronic absorption spectra are analysed and potential energy curves along a generalized coordinate combining several internal degrees of freedom involved in the isomerization process are determined and discussed. Our results are put in perspective with those obtained from recent picosecond/femtosecond time-resolved experiments. We provide a general mechanistic picture of the early steps of the process for this class of compounds. This contribution is the first theoretical “review” dedicated to the field of photoisomerizable Re(I) polypyridyl complexes.
Gesehen am 28.07.2022